The Bebek Putih Jambul Educational Value (Journal of Namibian Studies : History Politics Culture, 2023)
This article aims to discuss the educational values ​​of the Bebek Putih Jambul. The Bebek Putih Jambul is known as a new dance that has been created for young girls. However, many parents suspect that this new dance is just entertainment for toddlers. The problems : (1) What is the form of the Bebek Putih Jambul? (2) Is the Bebek Putih Jambul, as a new dance creation, educating children?. This new dance creation for toddlers was completed using R&D methods. All the data was obtained through observation, document study, and in-depth interviews with informan at Sanggar Paripurna. Data analysis was carried out qualitatively by applying reception and aesthetic theory. The results showed that : 1)  the Bebek Putih Jambul is a new dance creation that was especially created for early childhood. The themes, variety of movements, choreography, fashion make-up, and musical accompaniment of the performances are developed according to the children's physical and psycho-social development. The structure of the Bebek Putih Jambul includes : pepeson, pengawak, pengecet, and pekaad to the accompaniment of the Gamelan Semaradana; 2) It contains about tattwa, morals, rituals, as well as education about ethnic artistic creativity that is suitable for early childhood in Bali.